Mitochondrial DNMT3A and DNA methylation in skeletal muscle and CNS of transgenic mouse models of ALS - Wong, Margaret; Gertz, Barry; Chestnut, Barry A.; Martin, Lee J. (Frontiers in Cellular Neuroscience, 2013)
Cytosine methylation is an epigenetic modification of DNA catalyzed by DNA methyltransferases. Cytosine methylation of mitochondrial DNA (mtDNA) is believed to have relative underrepresentation; however, possible tissue and cell differences in mtDNA methylation and relationships to neurodegenerative disease have not been examined. We show by immunoblotting that DNA methyltransferase 3A (Dnmt3a) isoform is present in pure mitochondria of adult mouse CNS, skeletal muscle, and testes, and adult human cerebral cortex. Dnmt1 was not detected in adult mouse CNS or skeletal muscle mitochondria but appeared bound to the outer mitochondrial membrane. Immunofluorescence confirmed the mitochondrial localization of Dnmt3a and showed 5-methylcytosine (5mC) immunoreactivity in mitochondria of neurons and skeletal muscle myofibers. DNA pyrosequencing of two loci (D-loop and 16S rRNA gene) and twelve cytosine-phosphate-guanine (CpG) sites in mtDNA directly showed a tissue differential presence of 5mC. Because mitochondria have been implicated in the pathogenesis of amyotrophic lateral sclerosis (ALS), but the disease mechanisms are uncertain, we evaluated mitochondrial Dnmt3a and 5mC levels in human superoxide dismutase-1 (SOD1) transgenic mouse models of ALS. Mitochondrial Dnmt3a protein levels were reduced significantly in skeletal muscle and spinal cord at presymptomatic or early disease. Immunofluorescence showed that 5mC immunoreactivity was present in mitochondria of neurons and skeletal myofibers, and 5mC immunoreactivity became aggregated in motor neurons of ALS mice. DNA pyrosequencing revealed significant abnormalities in 16S rRNA gene methylation in ALS mice. Immunofluorescence showed that 5mC immunoreactivity can be sequestered into autophagosomes and that mitophagy was increased and mitochondrial content was decreased in skeletal muscle in ALS mice. This study reveals a tissue-preferential mitochondrial localization of Dnmt3a and presence of cytosine methylation in mtDNA of nervous tissue and skeletal muscle and demonstrates that mtDNA methylation patterns and mitochondrial Dnmt3a levels are abnormal in skeletal muscle and spinal cord of presymptomatic ALS mice, and these abnormalities occur in parallel with loss of myofiber mitochondria.